Exploring factors influencing e-health adoption and use among healthcare professionals in the clinical area in Sub-Saharan Africa: using Q-Methodology and models of technology acceptance - Ladan, Muhammad Awwal (2018)
Background: Despite the reported advantages of utilising healthcare technology within the clinical area in developed countries, there has been limited information on factors influencing e-health adoption and use in developing countries including sub-Saharan Africa. Thus, this study using Q-methodology provided insight into those salient factors that influences these group of participants’ choices about e-health adoption and use in their clinical practices.